A baby with café au lait spots: what to do. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2017)
The diagnosis of neurofibromatosis type 1 (NF1) is difficult in infancy when it is necessary to differentiate it from more frequent conditions such as hypermelanic nevus and rarer ones such as McCune-Albright syndrome. This is a retrospective clinical study that examines the frequency of known diagnostic criteria as plexiform neurofibroma and conditions such as juvenile xanthogranuloma that, although not yet considered a diagnostic criterion, greatly reinforce the suspicion of NF1. In a population of 94 children with café au lait spots as a sign of onset there was an affected parent in 4 cases, plexiform neurofibroma in 8 cases, juvenile xanthogranuloma in 9, nevus anemicus, dysmetry of a limb and congenital medium sized or giant melanocytic nevus respectively in 4 cases. Modalities of monitoring a baby with café au lait spots and suspected NF1 are suggested.